Working condition sensitivity analysis and optimal structure parameter determination of IVT based on CFD and orthogonal experiment - Fu, Cheng (2025)
To address liquid accumulation in horizontal gas wells, a specialized internal vortex tool (IVT) was developed for use in the horizontal sections, functioning as a drainage gas recovery device. This tool operates by leveraging centrifugal forces generated during fluid swirl to separate liquid from gas. The study examined the performance of IVT under various operational conditions and sought to identify optimal structural parameters. Through a controlled variable approach, the impact of inlet velocity and the water-gas volume ratio on pressure drop range, MGV (maximum gas velocity), and MVFLP (maximum liquid phase volume fraction) was analyzed. The results indicated that when the inlet velocity is between 2 and 4 m/s and the water to gas volume ratio is between 0.5 and 2m3/104 m3, the smaller the inlet velocity and the smaller the water to gas volume ratio, the better the gas-liquid separation effect of the IVT. An orthogonal test was subsequently employed to fine-tune the tool's structural parameters for different conditions, culminating in the creation of a comprehensive optimization chart for IVT. This study can effectively design drainage gas production tools for gas wells under different working conditions, reduce energy loss during drainage gas production, effectively utilize downhole resources, and achieve the goal of increasing natural gas well production and reducing costs.